Strengthened Democratic Legitimization of the European Union – Discussion in the Context of the European Citizens’ Initiative, New European Parliament Election System and National Parliaments’ Participation in the Process of European Integration (Economic and Political Thought, 2012)
There is no doubt that, as a result of the public finance crisis in all theEuro zone countries and also some other European Union member states,the European Union institutions once again strive to confirm their reliabilityboth in Europe and on the global arena. The Treaty of Lisbon, whichis being implemented, built formal foundations of changes that are aimedat that direction. It provides that the European Citizens’ Initiative will beintroduced, there will be a change in the European Parliament election systemand national parliaments will be given more rights in the EuropeanUnion decision-making process. Special attention should be paid to sparingno effort to show the European Union citizens that the European Unioncan be a real and effective formula for finding remedies for the crisis. Thestakes are high in this game. In fact, it is the question regarding the future ofthe European integration, i.e. whether it will be the Union of strengthenedpolitical cooperation around home market and the Euro zone or the Unionweakened by conservative nationalism focusing on suggestions made in somestates that it is necessary to search for alternative to the European ways offighting against the crisis.